Ammonia removal from aqueous solution by ion exchange using natural zeolite - Aral, N; Günay, A; Sevimoglu, O; Çali, M; Debik, E (INST LEBENSMITTELTECHNOLOGIE ANALYTISCHE CHEMIE, 1999)
The ammonia removal from aqueous solution by a natural ion exchange resin was investigated. The feasibility of natural zeolite usage as ion exchanger to remove ammonia and ion exchange capacity of natural zeolite were determined. Natural zeolites taken from Balikesir (Turkey) region were broken into pieces, a diameter of 2 mm, and the effect of different initial ammonia concentrations on ion exchange capacity was tested. According to experimental result, ion exchange capacity for 7.5 and 5 mg/l NH4+ initial ammonia concentration were found to be 4.5 and 1.7 mg NH4+/g resin, respectively.
Keywords: ammonia removal; natural zeolite; ion exchange; Environmental Sciences & Ecology